2023
DOI: 10.1038/s41598-023-40506-w
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a hybrid deep learning–machine learning approach for severity assessment of COVID-19 and other pneumonias

Doohyun Park,
Ryoungwoo Jang,
Myung Jin Chung
et al.

Abstract: The Coronavirus Disease 2019 (COVID-19) is transitioning into the endemic phase. Nonetheless, it is crucial to remain mindful that pandemics related to infectious respiratory diseases (IRDs) can emerge unpredictably. Therefore, we aimed to develop and validate a severity assessment model for IRDs, including COVID-19, influenza, and novel influenza, using CT images on a multi-centre data set. Of the 805 COVID-19 patients collected from a single centre, 649 were used for training and 156 were used for internal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Applying the experimental results to the 30% testing data (i.e., 2766 images out of 9220) demonstrates the superiority of the hybrid DTL approach when coupled with NN, achieving the highest MCC of 0.814, followed by SVM with a linear kernel, which yielded an MCC of 0.805 when compared to existing pre-trained models of densely connected classifiers in the binary classification task. Others have proposed deep learning approaches to detect COVID-19 using X-ray and CT images [9][10][11][12][13][14]. Table 1 provides an overview of the existing works compared to our proposed work.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…Applying the experimental results to the 30% testing data (i.e., 2766 images out of 9220) demonstrates the superiority of the hybrid DTL approach when coupled with NN, achieving the highest MCC of 0.814, followed by SVM with a linear kernel, which yielded an MCC of 0.805 when compared to existing pre-trained models of densely connected classifiers in the binary classification task. Others have proposed deep learning approaches to detect COVID-19 using X-ray and CT images [9][10][11][12][13][14]. Table 1 provides an overview of the existing works compared to our proposed work.…”
Section: Introduction and Related Workmentioning
confidence: 99%
“…This method divided the lung regions into several subdivisions and assigned scores ranging from 0-3. Another author in 35 created and validated a severity assessment model encompassing COVID-19, influenza, and novel influenza, utilizing CT images from a diverse multi-center dataset and reported that the developed model also applies to patients with other types of viral pneumonia. In the proposed architecture, we have employed the modified the RALE scoring system introduced 12 , 32 to assess COVID-19 CXR image severity.…”
Section: Introductionmentioning
confidence: 99%